The practice of traditional rituals and customs in newborns by mothers in selected villages in southwest Uganda - Beinempaka, Florence; Tibanyendera, Basil; Atwine, Fortunate; Kyomuhangi, Teddy; MacDonald, Noni E (Paediatrics & Child Health, 2014)
Between 1990 and 2011, neonatal mortality dropped from 32 to 22 per 1000 live births globally, but has remained above 30 per 1000 live births in Africa. Many neonatal deaths are preventable with support for healthy pregnancies, deliveries and newborn care. Continuation of traditional pregnancy/birth rituals may be placing some mothers/neonates at risk. The Ankole region of Uganda has a population of approximately eight million, and approximately 10,000 live referral hospital births annually. However, most babies are born at home in their villages because women avoid going to the hospital unless complications occur. The purpose of the present study was to determine what potentially harmful traditional pregnancy/birth rituals were practiced in the Ankole region, and to develop Village Health Team (VHT; volunteer community workers with limited health training) mitigation strategies.
Keywords: Traditional rituals; Newborns; Uganda